The Effects of Amniotic Nutrient Administration, "In ovo Feeding" of Arginine And/or β-Hydroxy- Betβ-Methyl Butyrate (HMB) on Insulin-like Growth Factors, Energy Metabolism and Growth in Turkey Poults - Foye, O.T.; Uni, Z.; McMurtry, J.P.; Ferket, P.R. (International Journal of Poultry Science, 2006)
In ovo feeding (IOF), injecting nutrients into the amnion, may improve growth performance by enhancing circulating IGF`s and glycogen reserves. To test this hypothesis 400 Hybrid® turkey eggs were injected into the amnion with 1.5 ml saline solutions consisting of 4 IOF formulation treatments consisting of a factorial arrangement of 2 levels of arginine (ARG 0 or 0.7%) and 2 levels of HMB (0 or 0.1%) at 23 days (d) of incubation. At hatch, poults were fed ad libitum and bodyweights (BW), organ weights, total liver and pectoralis muscle (PM) glycogen were taken at hatch 3, 7, 10, and 14 d. Additionally, hepatic glucose-6-phosphatase (G6P) activity was determined at hatch and 7 d. Heparinized blood samples were taken at hatch, 3 d, 7 d and 14 d and plasma was analyzed for IGF-I and IGF-II levels using an acid-ethanol extraction method. Although arginine had no affect on BW, there were significant main effects of HMB on increased BW from hatch through 14 d. Plasma IGF-I levels were significantly enhanced at hatch, 3 and 7 d in poults in ovo fed both ARG and HMB, but not when either factor was independent. Significant ARG X HMB effects were observed on IGF-II at hatch, 3d and 7d: without ARG, IGF-II was decreased by HMB, but it increased when added with ARG. All in ovo treatments increased G6P at hatch, while, G6P was depressed by HMB or ARG alone at 7 d. Total hepatic glycogen was increased only at hatch by HMB or ARG, but their effects were not additive as indicated by a significant ARG X HMB effect. In ovo administration of HMB and arginine enhances hepatic liver reserves, which may provide the fuel needed for rapid subsequent growth during the critical post-hatch period.